Bilingual Contexts Modulate the Inhibitory Control Network - Yang, Jing; Ye, Jianqiao; Wang, Ruiming; Zhou, Ke; Wu, Yan Jing (Frontiers in Psychology, 2018)
The present functional magnetic resonance imaging (fMRI) study investigated influences of language contexts on inhibitory control and the underlying neural processes. Thirty Cantonese–Mandarin–English trilingual speakers, who were highly proficient in Cantonese (L1) and Mandarin (L2), and moderately proficient in English (L3), performed a picture-naming task in three dual-language contexts (L1-L2, L2-L3, and L1-L3). After each of the three naming tasks, participants performed a flanker task, measuring contextual effects on the inhibitory control system. Behavioral results showed a typical flanker effect in the L2-L3 and L1-L3 condition, but not in the L1-L2 condition, which indicates contextual facilitation on inhibitory control performance by the L1-L2 context. Whole brain analysis of the fMRI data acquired during the flanker tasks showed more neural activations in the right prefrontal cortex and subcortical areas in the L2-L3 and L1-L3 condition on one hand as compared to the L1-L2 condition on the other hand, suggesting greater involvement of the cognitive control areas when participants were performing the flanker task in L2-L3 and L1-L3 contexts. Effective connectivity analyses displayed a cortical-subcortical-cerebellar circuitry for inhibitory control in the trilinguals. However, contrary to the right-lateralized network in the L1-L2 condition, functional networks for inhibitory control in the L2-L3 and L1-L3 condition are less integrated and more left-lateralized. These findings provide a novel perspective for investigating the interaction between bilingualism (multilingualism) and inhibitory control by demonstrating instant behavioral effects and neural plasticity as a function of changes in global language contexts.